A Systematic Approach to Patients with Jaundice - Gondal, Bilal; Aronsohn, Andrew (Seminars in Interventional Radiology, 2016)
Jaundice is a clinical manifestation of disorders of underlying bilirubin metabolism, hepatocellular dysfunction, or biliary obstruction. As clinical presentations of yellowing of eyes or skin can be somewhat nonspecific for the underlying etiology of disease, a stepwise approach to evaluation is necessary for accurate diagnosis and effective treatment plan. In this review, we discuss underlying mechanisms of cholestasis and jaundice as well as laboratory and imaging modalities needed to evaluate a patient presenting with hyperbilirubinemia. Jaundice occurs in settings of cholestasis or inability to effectively secrete bile as well as disorders of bilirubin metabolism and hepatocellular dysfunction. Clinical signs of jaundice occur when the serum bilirubin level exceeds 2.5 to 3 mg/dL. In all cases, evaluation begins with liver chemistry tests which include bilirubin (conjugated and unconjugated), alkaline phosphatase, alanine aminotransferase, aspartate aminotransferase, and total protein. In patients with hepatobiliary causes of jaundice, the alkaline phosphatase is usually elevated. In these cases, evaluation of hepatic synthetic function is crucial to the formulation of a treatment plant. When serologic evaluation is combined with hepatobiliary imaging, underlying mechanism of disease can often be elucidated. A stepwise approach to evaluation can be cost and time saving as well as a framework to improve patient outcomes. In this review, we will outline a diagnostic approach to jaundice, beginning with pathophysiology of cholestasis followed by hyperbilirubinemia and markers of synthetic dysfunction.
Keywords: jaundice; hyperbilirubinemia; cholestasis